A novel approach using streptavidin magnetic bead-sorted in vivo biotinylated survivin for monoclonal antibody production - Tayapiwatana C. (2014)
One major obstacle in antibody production is the lack of highly purified immunogen. In this study, we describe an alternative strategy to circumvent this problem. A nucleotide sequence encoding a full-length of human survivin was cloned into pAK400cb. After transforming into an E. coli Origami B strain, survivin-biotin carboxyl carrier protein (BCCP) fusion protein was generated in the cytoplasm, where the BCCP domain serves as a target for in vivo biotinylation. The biotinylated heterologous protein was subsequently immobilized on streptavidin-coated magnetic particles and separated from other proteins in a magnetic field. The survivin-coated beads were used to raise immune responses in BALB/c mice for hybridoma production. A number of hybrid clones were found to secrete anti-survivin antibodies. Three established clones were selected for single cell cloning. All generated monoclonal antibodies specifically reacted with the standard human recombinant survivin. Two out of three monoclonal antibodies recognized survivin in tumor extracts. The present method has advantages in facilitating monoclonal antibody production by making antigen purification steps unnecessary.